Pendekatan Pemecahan Masalah sebagai Strategi Pembelajaran Matematika di Sekolah Dasar - Unaenah, Een; Ilyasa, Nabila; Fazriah, Nurul; Uthantry, Zuanita Hershifani (Lembaga Yasin AlSys, 2023)
This research discusses many approaches to teaching mathematics to children, including problem solving techniques. It investigates the value of critical thinking skills for arithmetic investigations and demonstrates the benefits of using these techniques in an elementary school climate. This explanation thus goes a long way to managing critical thinking and how this approach can be used in numerical training. It also examines potential problems educators can see when implementing this framework and provides tips for implementing them. Overall, this paper showcases the importance of making assertive reasoning a profitable developmental experience in learning basic mathematics and providing pointers for teachers to try out instructive practices.